Out-of-hospital cardiac arrests and outdoor air pollution exposure in Copenhagen, Denmark. - Janine Wichmann (Public Library of Science (PLoS), 2013)
Cardiovascular disease is the number one cause of death globally and air pollution can be a contributing cause. Acute myocardial infarction and cardiac arrest are frequent manifestations of coronary heart disease. The objectives of the study were to investigate the association between 4 657 out-of-hospital cardiac arrests (OHCA) and hourly and daily outdoor levels of PM(10), PM(2.5), coarse fraction of PM (PM(10-2.5)), ultrafine particle proxies, NO(x), NO(2), O(3) and CO in Copenhagen, Denmark, for the period 2000-2010. Susceptible groups by age and sex was also investigated. A case-crossover design was applied. None of the hourly lags of any of the pollutants were significantly associated with OHCA events. The strongest association with OHCA events was observed for the daily lag4 of PM(2.5), lag3 of PM(10), lag3 of PM(10-2.5), lag3 of NO(x) and lag4 of CO. An IQR increase of PM(2.5) and PM(10) was associated with a significant increase of 4% (95% CI: 0%; 9%) and 5% (95% CI: 1%; 9%) in OHCA events with 3 days lag, respectively. None of the other daily lags or other pollutants was significantly associated with OHCA events. Adjustment for O(3) slightly increased the association between OHCA and PM(2.5) and PM(10). No susceptible groups were identified.